Acute Correction of Multiplanar Proximal Tibial Deformity Utilizing Fixator-Assisted Intramedullary Nailing. Issue 3 (31st July 2022) - Charla, Joseph Nicholas; Sharkey, Melinda S.
Abstract : Background: Proximal tibial deformities, particularly varus deformities, are relatively common in adolescents and young adults. The etiology of these deformities is often untreated or undercorrected infantile and adolescent Blount disease. Other less common etiologies include metabolic bone disease-associated deformities, posttraumatic and iatrogenic growth disturbance, and deformity related to surgical treatment or radiation for tumors 1 -3 . We apply the principles of fixator-assisted acute deformity correction, mostly described for use at the distal aspect of the femur, as well as the principles of anatomic reduction and fixation of proximal-third tibial fractures 4 to acutely correct these complex deformities in skeletally mature individuals 5 -12 . We perform acute correction of multiplanar proximal tibial deformity with use of fixator-assisted intramedullary nailing in order to avoid the complications and patient discomfort associated with gradual deformity correction with use of a circular external fixator. This procedure is novel in the treatment of adolescent Blount disease deformity in skeletally mature individuals and can additionally be utilized for other proximal tibial metaphyseal deformities, allowing the accurate and acute correction of all planes of deformity as well as the anatomic and mechanical axes, while avoiding the prolonged use of external fixators. Description: The patient is positioned supine on a radiolucent table. The locations of the proximal tibial osteotomy, fibular osteotomy, external fixator pin sites, and intramedullary nail insertion site are marked with use of a surgical marker and fluoroscopic imaging. Large external fixator half-pins are placed proximal and distal to the planned tibial osteotomy in both the anterior-posterior and sagittal planes, avoiding the path of the planned tibial intramedullary nail. A fibular osteotomy and then a low-energy tibial osteotomy are performed with use of multiple drill holes and an osteotome. Next, the bone deformity is fully corrected and held in the corrected alignment with the external fixators. Then, the opening drill for the intramedullary nail is introduced into the proximal aspect of the tibia over a guidewire, and blocking screws are placed in the coronal and sagittal planes of the proximal fragment next to the opening reamer. The intramedullary canal is then reamed over a ball-tipped guidewire to the desired diameter and the selected intramedullary nail is placed and secured with proximal and distal interlocking screws. Finally, the external fixators are removed. Alternatives: Alternative operative treatments include external fixation and gradual or acute deformity correction as well as fixator-assisted acute deformity correction and plate fixation 13 -16 . Rationale: Typically, a tibial osteotomy with gradual deformity correction with use of a circular fixator is employed for the treatment of these deformities 3, 17 . The literature shows this to be an effective technique for accurate correction of these complex proximal tibial deformities. With the advent of internal motorized lengthening nails, however, there have been increasing efforts to develop safe and accurate techniques for acutely correcting bone deformity so that these nails can be utilized to treat both angular deformities and bone-length differences simultaneously. Deformity at the proximal aspect of the tibia is often multiplanar, and complete correction of these deformities requires translation, angulation, and rotation through the osteotomy. An osteotomy performed at the proximal aspect of the tibia results in the equivalent of a proximal-third tibial fracture, which is more challenging and more demanding to fix than a diaphyseal tibial fracture because of the wide medullary canal and the strong deforming muscular forces at the proximal tibia. Fixator-assisted intramedullary nailing with blocking screws allows for the accurate correction of the mechanical and anatomic axes while avoiding external fixation. Expected Outcomes: The expected outcome is complete bone deformity correction and healing of the osteotomy site(s) 2 . Important Tips: Careful preoperative planning is essential to accurately correct the anatomic and mechanical axes in all planes. In cases of acute correction of severe bone deformities, consider prophylactic nerve decompression. When possible, avoid the use of a tourniquet in order to minimize tissue trauma, postoperative swelling, and the need for prophylactic fasciotomies. Obtain and hold perfect osseous alignment with use of temporary uniplanar external fixators prior to placing any definitive hardware. Acronyms and Abbreviations: AP = anteroposterior IM = intramedullary PACS = picture archiving and communication system K-wire = Kirschner wire CORA = center of rotation and angulation DVT = deep venous thrombosis PE = pulmonary embolism